Nano-pesticides - A recent approach for pest control (The Journal of Plant Protection Sciences, 2023)
Indiscriminate use of synthetic chemical pesticides has led to several environmental problems such as resistance  and environment pollution. Nanotechnology visualized as a rapidly evolving field has potential to revolutionize  agriculture and food systems. We utilized nano-technological interventions for developing nanopesticides with  potent fungicidal and miticidal properties. Nanosulphur and nanohexaconazole were prepared using encapsulation  technique. The Dynamic Light Scattering (DLS) studies, Scanning Electron Microscopy (SEM) and Transmission  Electron Microscopy (TEM) studies confirmed the nano-structure of nanopesticides. Nanoparticles of sulphur and  hexaconazole thus characterized were estimated for the presence of active ingredient in the formulation adopting  analytical techniques like Gas Chromatography / High Pressure Liquid Chromatography (HPLC). The bio-assay  studies revealed many fold improved activity of nanopesticides against fungi and mites as compared to commercial  sulphur.
Keywords: Nanotechnology; nanosulphur; nanohexaconazole; miticida; fungicidal; biosafety; analysis